The Use of Pentoxifylline Topical in the Treatment of Alopecia in Rats - Raad H. Hassan; Ahmed H. Jwaid (Institute of Medico-legal Publications Pvt Ltd, 2021)
Hair is the human body’s major esthetic display component, especially in cultural and social interactions.Hair loss is yet sometimes transient and the patient restore hair growth but have harmful effect on thepsychology of the patient. Throughout this research, the potency of topical pentoxifylline (PTX) instimulating regrowth in hair loss caused by cyclophosphamide was established. The study was performedby treated with PTX topically in male Swiss albino rats. The animals divided into seven groups with sixanimals in each group. To induce alopecia Cyclophosphamide used at a dose of (125 mg/kg) intraperitoneal.Macroscopically pentoxifylline (PTX) treated groups displayed new hair growth. Strong follicularproliferation was demonstrated by histopathology and gross morphological observations of hair growth inshaved areas. The blood biochemical cytokine assay revealed a down regulation of pro inflammatory TH1cytokines TNF-? and INF-g, in addition there is up regulation of TH2 cytokine IL-13. In the study showedan efficient efficacy on the treatment of alopecia induced by cyclophosphamide.